Human Insecurities in Southeast Asia
XI, 200 p. 9 illus.
Keywords: This book is a collection of work by scholars currently pursuing research on human security and insecurities in Southeast Asia. It deals with a set of ‘insecurities’ that is not readily understood or measurable. As such, it conceptually locates the threats and impediments to ‘human security’ within relationships of risk, uncertainty, safety and trust. At the same time, it presents a wide variety of investigations and approaches from both localized and regional perspectives. By focusing on the human and relational dimensions of insecurities in Southeast Asia it highlights the ways in which vulnerable and precarious circumstances (human insecurities) are part of daily life for large numbers of people in Southeast Asia and are mainly beyond their immediate control. Many of the situations people experience in Southeast Asia represent the real outcomes of a range of largely unacknowledged socio-cultural-economic transformations interlinked by local, national, regional and global forces, factors and interests. Woven from experience and observations of life at various sites in Southeast Asia, the contributions in this volume give an internal and critical perspective to a complex and manifold issue. They draw attention to a variety of the less-than-obvious threats to human security and show how perplexing those threats can be. All of which underscores the significance of multidisciplinary approaches in rethinking and responding to the complex array of conditioning factors and interests underlying human insecurities in Southeast Asia.